Long Lasting Cellular Immune Response Induced by mRNA Vaccination: Implication for Prevention Strategies - Vitiello, Laura; Gatta, Lucia; Ilari, Sara; Bonassi, Stefano; Cristina, Mario; Ciatti, Filippo; Fini, Massimo; Proietti, Stefania; Russo, Patrizia; Tomino, Carlo; Limongi, Dolores (Frontiers in Immunology, 2022)
As the COVID19 pandemic continues to spread and vaccinations are administered throughout the world at different rates and with different strategies, understanding the multiple aspects of the immune response to vaccinations is required to define more efficient vaccination strategies. To date, the duration of protection induced by COVID19 vaccines is still matter of debate. To assess whether 2-doses vaccination with BNT162b2 mRNA COVID-19 vaccine was sufficient to induce a persistent specific cellular immune response, we evaluated the presence of SARS-COV2 Spike-specific B and T lymphocytes in 28 healthcare workers 1 and 7 months after completing the vaccination cycle. The results showed that at 7 months after second dose a population of Spike-specific B lymphocytes was still present in 86% of the immunized subjects, with a higher frequency when compared to not-immunized controls (0.38% ± 0.07 vs 0.13% ± 0.03, p<0.001). Similarly, specific CD4+ and CD8+ T lymphocytes, able to respond in vitro to stimulation with Spike derived peptides, were found at 7 months. These results confirm that vaccination with BNT162b2 is able to induce a specific immune response, potentially long lasting, and could be helpful in defining future vaccination strategies.